Influence of Nickel Catalyst Morphology on Layer‐Exchange‐Based Carbon Crystallisation of Ni/a‐C Bilayers. Issue 11 (25th August 2017) - Janke, Daniel; Hulman, Martin; Wenisch, Robert; Gemming, Sibylle; Rafaja, David; Krause, Matthias
Abstract : Metal‐induced crystallisation with layer exchange is applied on Ni/C bilayer stacks deposited by three PVD techniques on SiO2 . The layer stacks were deposited at room temperature by either ion beam sputtering, direct current magnetron sputtering or high‐power impulse magnetron sputtering. The influence of the Ni morphology on the layer exchange degree α LE and the resulting graphitic ordering is studied by atomic force microscopy, Rutherford backscattering spectrometry and Raman spectroscopy. The initial RMS roughness of the Ni top layer varied with the deposition technique by a factor of 20, from 0.3 to 6.1 nm. After annealing in UHV at up to 700 °C, layer exchange was observed for all samples. Still, the layer exchange degree was affected by the roughness of the initial bilayer stack. The highest value of 96% was achieved for magnetron‐sputtered samples, what is by ∼35% higher than for the initially roughest Ni surfaces. Raman spectroscopy showed the formation of graphitic carbon, characterised by a strong 2D line, for all three bilayer stacks. The degree of graphitic ordering increased with decreasing Ni surface roughness. Abstract : Nickel‐induced crystallisation of amorphous carbon is analysed by AFM, RBS and Raman spectroscopy. A special focus lays on the influence of the catalyst's morphology on the layer exchange and the quality of the crystalline layer after the annealing experiment at 700 °C. The layer exchange degree is introduced as a quantitative criterion for this type of processes for the first time.